Stéphanos Xénos (1821-1894) - Zéphyros Kafkalidis (Cahiers Balkaniques)
Son of a merchant family from Smyrna, Xenos should have made a career in trade or in the Greek army. In his life, he was entrepreneur, writer, shipowner, industrial, bold and innovative, he wanted to open a new world and to renovate Greece I order to make it stronger. But, impatient as he is, he gets angry with everybody, he mixes the deep feeling, here patriotism, with business and politics, that’s his specificity, his greatness but also his loss, because money, politics and feelings rarely collaborate.